Hasil dan Kualitas Okra (Abelmoschus esculentus L. Moench.) Merah dan Okra Hijau dengan Jenis Pupuk yang Berbeda - Manik, Auhge Eva Sari; Melati, Maya; Kurniawati, Ani; Faridah, dan Didah Nur (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Okra fruit contains phenolic compounds as natural antioxidant. The aim of this research was to analyze the effect of different types of fertilizers on production and quality of two okra varieties. The experiment was conducted in October 2017 to February 2018 at Bogor Agricultural University experimental field at Leuwikopo, Darmaga, Bogor (-6033’49.3”SL, 106043’30.7’’EL). The experiment used nested randomized complete block design with 2 factors and 4 replications. The first factor consisted of two okra varieties with different colour (red and green okra). The second factor was fertilizer types consisted of no fertilizer, organic (cow manure), combination of organic + inorganic, and inorganic fertilizer. The results showed that fertilizer types significantly affected plant height and fruit N content but did not affect fruit production. Red okra had a higher plant height, lower number of leaves and leaf K content than those of the green okra. The interaction effect of both factors was significant on total phenolic content in fruit and P content in leaf. The highest total phenolic content in fruit was showed by red okra with inorganic fertilizer, although it was not significantly different to those of red okra with combination organic + inorganic fertilizer, and also to green okra with organic fertilizer. The highest P content in leaf was found in red okra without fertilizer, however it was not significantly different to red okra with combination organic + inorganic fertilizer, green okra with organic fertilizer, and green okra with inorganic fertilizer.Keywords: inorganic fertilizer, leaf nutrient, organic fertilizer, phenolic compound